If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5x = 19 + x Solving 3 + 5x = 19 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 5x + -1x = 19 + x + -1x Combine like terms: 5x + -1x = 4x 3 + 4x = 19 + x + -1x Combine like terms: x + -1x = 0 3 + 4x = 19 + 0 3 + 4x = 19 Add '-3' to each side of the equation. 3 + -3 + 4x = 19 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 19 + -3 4x = 19 + -3 Combine like terms: 19 + -3 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 3x+40=10x-37 | | 11x-14=7x+2 | | 6x^2-35x-9=0 | | 5y^3+128=0 | | 12x-6+4x= | | 5x^2+26x+24=0 | | 10a+10b=8c | | 6y+8=2y+3 | | -8-4x=1-x | | x-15=4x | | 16x+8-12x+6=18x+9 | | 7n=2n-20 | | y^2=x^3+9x+17 | | a+(5+3a)=2a-7 | | 4(2x+3)=2(5x-2)+6 | | 9-6y=24-8y+7 | | 3t^2=6t-12 | | 4y-7+2y=5y-6+9 | | 13-2x= | | x-5y=3v | | 2x+5=3x+10 | | 3a-4=A | | 2x-20=5x-5 | | 189-5x=31x+17 | | -35-4x=13-10x | | 51-3x=7x+21 | | 6x+14=91-5x | | 6x+36=14x-52 | | (6x-5)(6x-5)=36x-25 | | 2a+2b+2c=262 | | 2n-20=7n | | 6x^2-10x+1=0 |